2013
DOI: 10.1111/1750-3841.12236
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparison of the Pungent Components in Commercial Zanthoxylum bungeanum Oil and Zanthoxylum schinifolium Oil

Abstract: In the present study, the characterization and comparison of the pungent components in commercial Z. bungeanum oils and Z. schinifolium oils were investigated. By high-performance liquid chromatography (HPLC)-mass spectrometry (MS/MS) analysis, the major alkylamides in Z. bungeanum and Z. schinifolium oils were identified as hydroxy-ε-sanshool, hydroxy-α-sanshool, hydroxy-β-sanshool, hydroxy-γ-sanshool, hydroxy-γ-isosanshool, bungeanool, isobungeanool, and tetrahydrobungeanool, respectively. Hydroxy-α-sanshool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 18 publications
4
35
0
Order By: Relevance
“…23 The alkylamides (10 mg mL −1 in methanol) were analyzed using a Shimadzu LC-20A system (Shimadzu Corp., Tokyo, Japan) equipped with a diode array detector (DAD) and an API 4000 QTRAP mass spectrometer system (AB Sciex, Darmstadt, Germany). 23 The alkylamides (10 mg mL −1 in methanol) were analyzed using a Shimadzu LC-20A system (Shimadzu Corp., Tokyo, Japan) equipped with a diode array detector (DAD) and an API 4000 QTRAP mass spectrometer system (AB Sciex, Darmstadt, Germany).…”
Section: Alkylamide Extraction and Identificationmentioning
confidence: 99%
“…23 The alkylamides (10 mg mL −1 in methanol) were analyzed using a Shimadzu LC-20A system (Shimadzu Corp., Tokyo, Japan) equipped with a diode array detector (DAD) and an API 4000 QTRAP mass spectrometer system (AB Sciex, Darmstadt, Germany). 23 The alkylamides (10 mg mL −1 in methanol) were analyzed using a Shimadzu LC-20A system (Shimadzu Corp., Tokyo, Japan) equipped with a diode array detector (DAD) and an API 4000 QTRAP mass spectrometer system (AB Sciex, Darmstadt, Germany).…”
Section: Alkylamide Extraction and Identificationmentioning
confidence: 99%
“…Sichuan pepper contains many phytochemicals. It was found that essential oils (e.g., linalool and limonene) (Yang, ) and alkylamides (e.g., α‐hydroxysanshool) (Zhao et al, ) are major components in Sichuan pepper. Flavonoids and phenols are other key compounds found in it.…”
Section: Discussionmentioning
confidence: 99%
“…It is also applied externally to treat eczema and pruritus. Essential oils (e.g., linalool and limonene) (Yang, ) and alkylamides (e.g., α‐hydroxysanshool) (Zhao et al, ) are major components in Sichuan pepper. Pharmacological research studies indicate that the extract of Sichuan pepper and its major compounds are effective for the treatments of inflammatory diseases (Tezuka et al, ), asthma (Tang, Xie, Guan, Jin, & Zhao, ), and Alzheimer's disease (Tang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Zanthoxylum is the largest and the most widespread genus in the Rutaceae, comprising approximately 250 species, and is widely distributed in the temperate and tropical regions, of which there are 45 species and 13 varieties in China [12,13]. Traditionally, members of them with pungent taste are often used as condiments in both Eastern Asian countries and Central America [14].…”
Section: Introductionmentioning
confidence: 99%